RELATION BETWEEN CAUSES OF HOSPITALIZATION AND SELF-CARE IN OLDER ADULTS WITH DIABETES MELLITUS 2 - Figueiroa, Viviana Patricia Manão; Echevarría-Guanilo, Maria Elena; Fuculo Junior, Paulo Roberto Boeira (My University, 2020)
ABSTRACT Objective: to analyze the relationship between self-care and the causes of hospitalization, in older adults with Diabetes mellitus 2. Method: quantitative, descriptive approach. Adults over 60 years old and older, hospitalized in medical and surgical centers, attended from August to December 2018, due to diabetes complications, A characterization instrument and the Older Adult Self-Care Capacity and Perception Test was applied. Descriptive, central tendency and relationship analyses were applied. Results: 32 people participated, 18 (56.3%) of whom were men. The years of diagnosis averaged 17.1 years (SD=12.6), 13 people (31.7%) were admitted to hospital for diabetic foot problems and 10(24.4%) for metabolic disorders. In relation to the Capacity and perception of self-care, 8(25%) presented an adequate self-care perception, 16(50%) a partially adequate self-care perception and 8(25%) without a partial deficit self-care capacity. There was a significant association between self-care and belonging to a social group (p=0.009). There was no statistical association between Capacity and perception of self-care and the causes of hospitalization: diabetic foot (p=0.587) and metabolic disorder (p=0.225). Seven of the eight dimensions showed a higher frequency of adequate self-care, but there was a higher percentage of a poor self-care 12(37.5%) in physical activity. Conclusions: no relationship was identified between capacity and perception of self-care and causes of hospitalization, meanwhile, there were low perceptions and deficits of self-care. The study of self-care in this type of patient is relevant and allows us to intervene in poor aspects or deficits.
Keywords: diabetes mellitus; older adult; self-care; hospitalization; nursing